Prevention of suicide with regulations aimed at restricting access to highly hazardous pesticides: a systematic review of the international evidence - Prof David Gunnell, DSc; Duleeka Knipe, PhD; Shu-Sen Chang, PhD; Melissa Pearson, PhD; Prof Flemming Konradsen, PhD; Prof Won Jin Lee, PhD; Prof Michael Eddleston, ScD (Elsevier, 2017)
Background: Pesticide self-poisoning accounts for 14-20% of suicides worldwide. Regulation aimed at restricting access to pesticides or banning highly hazardous pesticides is one approach to reducing these deaths. We systematically reviewed the evidence of the effectiveness of pesticide regulation in reducing the incidence of pesticide suicides and overall suicides. Methods: We did a systematic review of the international evidence. We searched MEDLINE, PsycINFO, and Embase for studies published between Jan 1, 1960, and Dec 31, 2016, which investigated the effect of national or regional bans, and sales or import restrictions, on the availability of one or more pesticides and the incidence of suicide in different countries. We excluded other interventions aimed at limiting community access to pesticides. We extracted data from studies presenting pesticide suicide data and overall suicide data from before and after national sales restrictions. Two reviewers independently assessed papers for inclusion, extracted data, and assessed risk of bias. We undertook a narrative synthesis of the data in each report, and where data were available for the years before and after a ban, we pooled data for the 3 years before and the 3 years after to obtain a crude estimate of the effect of the ban. This study is registered through PROSPERO, number CRD42017053329. Findings: We identified 27 studies undertaken in 16 countries-five low-income or middle-income countries (Bangladesh, Colombia, India, Jordan and Sri Lanka), and 11 high-income countries (Denmark, Finland, Germany, Greece, Hungary, Ireland, Japan, South Korea, Taiwan, UK, and USA). Assessments largely focused on national bans of specific pesticides (12 studies of bans in six countries-Jordan, Sri Lanka, Bangladesh, Greece [Crete], South Korea, and Taiwan) or sales restrictions (eight studies of restrictions in five countries- India, Denmark, Ireland, the UK and the USA). Only five studies used optimum analytical methods. National bans on commonly ingested pesticides in five of the six countries studied, including four studies using optimum analytical methods, were followed by reductions in pesticide suicides and, in three of these countries, falls in overall suicide mortality. Greece was the only country studied that did not show a decrease in pesticide suicide following a ban. There were no high-quality studies of restricting sales to people for occupational uses; four of the seven studies (in three of the five countries studied-India, Denmark, and the USA) showed sales restrictions were followed by decreases in pesticide suicides; one of the two studies investigating trends in overall suicide mortality reported a fall in deaths in Denmark, but there were also decreases in suicide deaths from other methods. Interpretation: National bans on highly hazardous pesticides, which are commonly ingested in acts of self-poisoning, seem to be effective in reducing pesticide-specific and overall suicide rates. Evidence is less consistent for sales restrictions. A worldwide ban on the use of highly hazardous pesticides is likely to prevent tens of thousands of deaths every year. Funding: None.